Characterizing phytoplankton biomass seasonal cycles in two NE Atlantic coastal bays - Santos, Mariana (2020)
The seasonal and interannual variability of chlorophyll a was studied between 2008 and 2016 in two coastal bays located in the northeastern limit of the Iberia/Canary upwelling ecosystem. The work aims (i) to understand if small latitudinal distances and/or coastline orientation can promote different chlorophyll a seasonal cycles; and (ii) to investigate if different meteorological and oceanographic variables can explain the differences observed on seasonal cycles. Results indicate three main biological seasons with different patterns in the two studied bays. A uni-modal pattern with a short early summer maximum and relatively low chlorophyll a concentration characterized the westernmost sector of the South coast, while a uni-modal pattern characterized by high biomass over a long period, slightly higher in spring than in summer, and high chlorophyll a concentration characterized the central West coast. Comparisons made between satellite estimates of chlorophyll a and in situ data in one of the bays revealed some important differences, namely the overestimation of concentrations and the anticipation of the beginning and end time of the productive period by satellite. Cross-correlation analyses were performed for phytoplankton biomass and different meteorological and oceanographic variables (SST, PAR, UI, MLD and precipitation) using different time lags to identify the drivers that promote the growth and the high levels of phytoplankton biomass. PAR contributed to the increase of phytoplankton biomass observed during winter/midspring, while upwelling and SST were the main explanatory drivers to the high Chl-a concentrations observed in late-spring/summer. Zonal transport was the variable that contributed most to the phytoplankton biomass during late-spring/summer in Lisbon Bay, while the meridional transport combined with SST was more important in Lagos Bay.